Thirty-day results from the ZEPHYR registry: outcomes of EVAR using the Zenith Alpha abdominal endovascular graft for the treatment of AAA in 347 patients - Hatzl, Johannes; Batenburg, Michiel Van Basten; Yeung, Kak K.; Fioole, Bram; Verhoeven, Eric L. G.; Lauwers, Geert; Kölbel, Tilo; Wever, Jan J.; Scheinert, Dierk Wolfgang; Van den Eynde, Wouter; Rouhani, Guido; Mees, Barend M. E.; et al. (Annals of vascular surgery, 2022)
Background - To report technical and clinical 30-day results following treatment with the Zenith Alpha™ abdominal stent graft from the ZEnith alPHa for aneurYsm Repair Registry (ZEPHYR). - Methods - Multicenter, nonrandomized, single arm, core laboratory-controlled, prospective registry collecting data on the Zenith Alpha Abdominal Endovascular Graft being used in subjects with abdominal aortic aneurysms (AAA) from sites in Germany, Belgium, and The Netherlands between December 2016 and December 2019. Inclusion criteria were non-ruptured AAAs with a maximum diameter ≥50 mm or enlargement >5 mm over 6 months with an AAA neck length ≥10 mm (site reported). Primary outcome measure was treatment success at 30 days. Treatment success was defined as a combined endpoint consisting of technical and clinical success. Technical success was defined as successful stent graft delivery and deployment as well as successful removal of the delivery system. Clinical success at 30 days was defined as freedom from type I and III endoleak, aneurysm rupture, conversion to open surgery and stent graft occlusion. - Results - Three hundred forty-seven subjects were included from 14 sites with a median age of 73.0 years (IQR 68.0-79.0). Thirty-four patients were female (9.8%). The median AAA diameter was 58.3 mm (IQR 55.0-63.5). The median proximal neck diameter was 23.6 mm (IQR 22.0-25.2) with a median proximal neck length of 24.4 mm (IQR 15.0-34.8) and a median infrarenal neck angulation of 24.5° (IQR 15.0-35.0). The right and left common iliac diameter were 16.1 mm (IQR 14.1-19.4) and 16.2 mm (IQR 14.1-19.1), respectively. The treatment success rate at 30 days was 94.8% (N = 329). Technical success was achieved in 333 patients (96.0%). The clinical success rate at 30 days was 98.8% (N = 343). Three patients had limb occlusions at 30 day follow up (0.9%). One patient had a type Ib endoleak (0.3%). Seventy percent of vascular access approaches were percutaneous. The reintervention rate was 1.7% (N = 6) within 30 days. Indications for reinterventions were a false aneurysm at puncture site (N = 1), limb complications (N = 2), stentgraft-associated renal artery occlusions (N = 2), and an external iliac artery thrombosis (N = 1). - Conclusions - Endovascular aneurysm repair using the Zenith Alpha Abdominal Endovascular Graft is effective in the short term. Long term results will be reported in the future.
Available online 30 August 2021
Gesehen am 10.01.2023